Rethinking urban spatial resource allocation during public health emergencies: assessing comfortable quarantine environment in Guangzhou Hotels - Yu-Yi Zheng; Jing-Yang Lin; Lai-Chun Zhao; Lei Xiong; Bo-Wei Zhu; Gwo-Hshiung Tzeng (Journal of Asian Architecture and Building Engineering)
In response to public health emergencies, many regions have requisitioned daily travel hotels as temporary quarantine places. However, few previous studies examine this policy and reflect on the rationality of urban spatial resource allocation and utilization in terms of comfort during quarantine. This study uses a hybrid multi-attribute decision-making model, based on the collection of 438 pieces of evaluation data about the comfort of isolation hotels in Guangzhou, to build an evaluation framework for the comfort of the quarantine environment. Then, this study uses the ANP-V technique to complete the performance evaluation of selected cases and combines the epidemic spread data in Guangzhou to explore the rationality and improvement strategies of local government epidemic prevention resource allocation and utilization. Based on the results of this study, local decision-makers can optimize the allocation of future epidemic prevention resources and minimize the negative impact on personal health during the emergency period.